A Companion to Late Medieval and Early Modern Siena
1 online resource.
Keywords: A Companion to Late Medieval and Early Modern Siena presents chapters by prominent scholars on the powerful commune that birthed a pope, sheltered saints, built banking institutions that have thrived for nearly 1000 years, and nurtured vibrant communities of artists and intellectuals. This multi-disciplinary book, edited by Santa Casciani and Heather Richardson Hayton, redresses scholarly imbalances of the past by introducing early period Siena to a wider audience. Focusing mostly on the 12th to 16th centuries, each chapter explores how the Sienese crafted a distinctive civic identity that remains intact still. Modern readers will find Siena's responses to plague, political factionalism, and aggression from powerful neighbours particularly relevant. .